A guide to reproduction social issues and human concerns - Pollard, Irina (Cambridge University Press, 1994)
The purpose of this comprehensive text is to increase awareness of human reproduction and its consequences. The central theme links reproductive capacity, the social consequences of the multiple stresses this places on the environment and the ways this relates back to the reproductive health of humans and other animals. In the first section, the biology of human reproduction is discussed, including such topics as the treatment and causes of infertility, growth and maturation, parental behaviour and neonate biology. The effects of procreational biology on the foundation of human social structure are also examined. The second part deals with reproduction as it relates to health and social issues such as stress, fertility control, AIDS, teratogens and errors of sexual differentiation. It is an invaluable resource for all those wishing to update their knowledge of human reproductive biology